PENGEMBANGAN BUKU SISWA DIGITAL BUKU CERITA BERGAMBAR SUBTEMA 2 UNTUK SISWA KELAS V SDN KALIBATA 11 PAGI - SULISTYANI PUTERI RAMADHANI; ADE AYU WULANDARI (Universitas Trilogi, 2022)
This study aims to produce a digital student book based on picture story books that is theoretically valid and effective for use for grade 5 elementary school students. This research was conducted using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The results of the product validation values that were validated by design experts were 83%, material experts 96% and linguists 90%. From this score, an average score of 89% is obtained, the textbook product is categorized as feasible to use. The level of product feasibility based on the one-on-one evaluation stage by the VB class teacher got a score of 100% and the small group trial by 20 class VB students at SDN Kalibata 11 Pagi got a score of 83%. From this score, the average score of 91% of the textbook products is categorized as feasible to use. With the existence of a picture story book-based textbook in which the book is dominated by interesting and fun pictures, it will have a positive impact on students. Students will really understand learning if they use textbooks based on picture story books.